2022
DOI: 10.3389/fmicb.2022.847449
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antibacterial and Anti-biofilm Effects of Vitamin C Against Pseudomonas aeruginosa Clinical Isolates

Abstract: There is a persistent need to look for alternative therapeutic modalities to help control the pandemic of antimicrobial resistance. Assessment of antibacterial and anti-biofilm effects of vitamin C (ascorbic acid) was the aim of the current study. The micro-dilution method determined the minimal inhibitory concentration (MIC) of ascorbic acid or antibiotics alone and in combinations against Pseudomonas aeruginosa (P. aeruginosa) clinical isolates. The micro-titer plate method monitored the effect of ascorbic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 32 publications
3
21
0
2
Order By: Relevance
“…Finally, AA may downregulate antibiotic-resistant genes. Our results were supported by the previous studies [ 45 , 46 ]…”
Section: Discussionsupporting
confidence: 93%
“…Finally, AA may downregulate antibiotic-resistant genes. Our results were supported by the previous studies [ 45 , 46 ]…”
Section: Discussionsupporting
confidence: 93%
“…These MIC and MBC result variations may be due to the susceptibility pattern of the S. mutans strains used, the purity of ascorbic acid, and the experimental settings carried out in different laboratories. Ascorbic acid at a sub-inhibitory dose of 19.5-312.5 mg/ml demonstrated 100% anti-biofilm activity and also displayed downregulation of antibiotic resistance genes against Pseudomonas aeruginosa 35 . It is reported that in clinical setting, antibiotic therapy should be prescribed along with ascorbic acid for routine bacterial infection treatment 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Ascorbic acid at a sub-inhibitory dose of 19.5-312.5 mg/ml demonstrated 100% anti-biofilm activity and also displayed downregulation of antibiotic resistance genes against Pseudomonas aeruginosa 35 . It is reported that in clinical setting, antibiotic therapy should be prescribed along with ascorbic acid for routine bacterial infection treatment 35 . In our study, ascorbic acid at a sub-MIC concentration (6.25 mg/ml) displayed no significant change in growth rate pattern and is in agreement with the results of Eydou et al, 34 reporting that there is no statistically significant difference in the growth rate pattern among the control and ascorbic acid treated at 1/2 sub-MIC (5.61 mg/ml) against S. mutans.…”
Section: Discussionmentioning
confidence: 99%
“…A concentration below the MIC (4 μg/mL) of ellagic acid reduced biofilm development of Streptococcus dysgalactiae NCTC 4671 up to 27% and S. dysgalactiae ATCC 27957 up to 21%, but 4 μg/mL had no effect on S. aureus biofilm growth [ 18 ]. In addition, even with the same phytocompound, it is not always possible to gather unique conclusions as different investigations were often carried out with variations in the methodologies, i.e., differences in sub-lethal doses, microbial targets, microbial cell density, and culture media [ 19 ]. Time could also be a key factor.…”
Section: Sub-lethal Concentrations Of Antibiofilm Phytochemicals As A...mentioning
confidence: 99%
“…Upon 40 μg/mL quercetin treatment, Klebsiella pneumoniae , P. aeruginosa and Yersinia enterocolitica displayed a >90% increase in sensitivity to tetracycline, kanamycin, and gentamycin [ 24 ]. According to Abdelraheem et al [ 19 ], vitamin C (ascorbic acid) had a synergistic effect with antibiotics against P. aeruginosa both in vitro and in vivo. The authors suggested that vitamin C should be consistently prescribed with antibiotics to treat Pseudomonas infections to reduce treatment duration and antibiotic dose.…”
Section: Sub-lethal Concentrations Of Antibiofilm Phytochemicals As A...mentioning
confidence: 99%